Universal RNA Secondary Structure Insight Into Mosquito-Borne Flavivirus (MBFV) cis-Acting RNA Biology - Miao Zeng; Yanping Duan; Wei Zhang; Mingshu Wang; Mingshu Wang; Mingshu Wang; Renyong Jia; Renyong Jia; Renyong Jia; Dekang Zhu; Dekang Zhu; Dekang Zhu; et al. (Frontiers in Microbiology, 2020)
Mosquito-borne flaviviruses (MBFVs) spread between vertebrate (mammals and birds) and invertebrate (mosquitoes) hosts. The cis-acting RNAs of MBFV share common evolutionary origins and contain frequent alterations, which control the balance of linear and circular genome conformations and allow effective replication. Importantly, multiple cis-acting RNAs interact with trans-acting regulatory RNA-binding proteins (RBPs) and affect the MBFV lifecycle process, including viral replicase binding, viral RNA translation-cyclisation-synthesis and nucleocapsid assembly. Considering that extensive structural probing analyses have been performed on MBFV cis-acting RNAs, herein the homologous RNA structures are online folded and consensus structures are constructed by sort. The specific traits and underlying biology of MBFV cis-acting RNA are illuminated accordingly in a review of RNA structure. These findings deepen our understanding of MBFV cis-acting RNA biology and serve as a resource for designing therapeutics in targeting protein-viral RNA interaction or viral RNA secondary structures.